Portable Doc Case / Noor Farah Diyanah Ismail - Ismail, Noor Farah Diyanah (2020)
In this current situation, people like the thing that can ese their life. In order to fulfil the demand, I came out with the idea of Portable Doc Case. I focus on worker and student population which are still using a bag to their office or campus. Therefore, we have designed the product suitable to customers need. Plus, the Portable Doc Case have many advantages compared to others common briefcase because we develop some new function such as many compartments, have searching code, attachable and not easily torn. Our product has great quality and technology that can satisfying people. We applied the hardy and light element because it will ease our customer to bring it anywhere, they go. Furthermore, we provide the affordable price with high quality material and provide long lasting product. We develop some new function to overcome the problem from previous issues that happen when use the common briefcase. People do not have to worry about the future problem because we provide great function from our briefcase. Other than that, we implement with interesting design that will attract people to use and easy to carry wherever they bring.